Sustainable concrete with additions of nano-materials and nano-bamboo charcoal / Norizzati Ibrahim and Che Maznah Mat Isa - Ibrahim, Norizzati; Mat Isa, Che Maznah (2020)
Nanomaterial concrete is new generation of concrete formed of materials in nanoscale. This research aims to investigate the strength of concrete with addition of nanomaterials. The material used in this research were Nano-Bamboo Charcoal (NBC) of size 10-140 nm, Ordinary Portland Cement (OPC), fine sand size of 50-650 um, and coarse aggregate in 5-10 mm. The portion of NBC are 3% and 10% based on the portion of cement weight. The addition of natural NBC could be a way to improve concrete durability and also sustainable construction. The focus of this research is utilizing the NBC in concrete. Furthermore, it is encourage using the renewable resources as building materials for continuing availability of building materials. This research aims to investigate the compressive strength of concrete by various portion addition of NBC based on cement weight. The results shows that concrete blocks with 3% NBC content showed better strength than those 10% NBC content. However, results of the control concrete of Grade 20 (0% replacement of NBC) show that lowest compressive strength compares to concrete which used NBC. Furthermore, a maximum strength of 38 N/mm2 was achieved when the NBC content was 3% together with 0.40 moisture content as compare with normal concrete which is only 20 N/mm2 only.